Pemetaan Serangan Penyebab Penyakit Busuk Batang Jagung di Kabupaten Tanah Laut, Kalimantan Selatan - Winda Rizky Oktaviani; Salamiah Salamiah; Dewi Fitriyanti (www.ulm.ac.id, 2023)
This study aims to determine the existence and distribution and extent of stem rot disease in maize in Tanah Laut District, South Kalimantan. This research was conducted from March to July 2022. Sampling was carried out in 10 sub-districts in Tanah Laut Regency, namely Bajuin, Batu Ampar, Bati-bati, Kintap, Kurau, Panyipatan, Pelaihari, Takisung and Tambang Lagi sub-districts which grow corn from 11 districts in Tanah Laut Regency. Observation of sample plants was carried out by observing the symptoms in each sub-district which were taken from three villages that planted corn and from each village 3 corn planting locations were taken. Each village which is the sample point consists of 5 samples taken diagonally. Each point consisted of 100 corn plants so that the number of plants observed at each planting location was 500 plants. Based on the results of observations the causes of corn stem rot caused by fungi and bacteria are spread in all sub-districts that grow corn in Tanah Laut Regency with various attack intensities.